Deposit market concentration and monetary transmission: Evidence from the euro area - Stephen Kho (European Central Bank (ECB), 2024)
I study the transmission of monetary policy to deposit rates in the euro area with a focus on asymmetries and the role of banking sector concentration. Using a local projections framework with 2003-2023 country-level and bank-level data for thirteen euro area member states, I find that deposit rates respond symmetrically to an unexpected tightening or easing of monetary policy. However, more concentrated domestic banking sectors do pass-on unexpected monetary tightening (easing) more slowly (quickly) than less concentrated banking sectors, which contributes to a temporary divergence of deposit rates across the euro area. These results suggest that heterogeneity in the degree of banking sector concentration matters for the transmission of monetary policy to deposit rates, which in turn may affect banking sector profitability.
Keywords: D40; E43; E52; G21; 330; Monetary policy; deposit rates; banking sector; market power